Pengembangan Media Audio-Visual Berorientasi Tpack Dalam Pembelajaran Senam Bugar Ceria Yang Dapat Meningkatkan Motorik Anak - Oetari Lismana; Yulva Andresta; Fero Kawa; Sapriyanto Sapriyanto (Jurnal Pendidikan Indonesia, 2025)
The objectives of this study are to: (1) develop Tpack-oriented audio-visual media in learning cheerful fitness gymnastics that can improve children's motor skills (2) describe the effectiveness of Tpack-oriented audio-visual media in learning cheerful fitness gymnastics that can improve children's motor skills. The subjects of this study are 30 children aged 5-6 years from PAUD Aisyah, Lubuk Unen Village, Merigi Kelindang District, Bengkulu Tengan Regency, Bengkulu Province, the focus of this research is Tpack-oriented audio-visual media in learning cheerful fitness gymnastics that can improve children's motor skills. This research was conducted with a "research and development" approach. The goal of research and development is to discover, develop and validate products, so that research can be sustainable. Research and development is the process of producing new products and testing the effectiveness of those products. Based on the analysis used in this study, the following results were obtained: (1) Tpack-oriented audio-visual media in learning cheerful fitness gymnastics that can improve children's motor skills is considered as a concrete platform and attracts children's attention to improve children's motor skills. (2) Tpack-oriented audio-visual media model in cheerful fitness gymnastics learning that can improve children's motor skills is developed as a good type of media as a learning tool to improve the motor skills of PAUD Aisyah children, Lubuk Unen Village, Merigi Kelindang District, Central Bengkulu Regency, Bengkulu Province. Significant improvement in motor ability based on the results of the t-test with a significance level of 0.00 less than 5%. The use of Tpack-oriented audio-visual media in learning cheerful fitness gymnastics that can improve children's motor skills. After using Tpack-oriented audio-visual media in learning cheerful fitness gymnastics that can improve children's motor skills, children's motor skills are higher than before using Tpack-oriented audio-visual media in learning cheerful fitness gymnastics that can improve children's motor skills